Fighting Back Against Anti-Asian Xenophobia: Addressing Global Issues in a Distance Learning Classroom - Dara Nix-Stevenson; Laura Shelton; Jennifer Smith (Middle Grades Review, 2020)
This practitioner essay will outline a project designed by a team of three critical educators at The Experiential School of Greensboro (TESG), a new grassroots charter school in Greensboro, North Carolina. In this essay, we will describe the social context of TESG, discuss how we built towards addressing complicated topics related to systemic racism, and outline the ways we addressed anti-Asian racism and xenophobia in a remote learning context during the COVID-19 pandemic.
Keywords: xenophobia; social justice; racism; COVID-19; social studies education; global education; content integration